Faecal Calprotectin from Ileostomy Output Is Sensitive and Specific for the Prediction of Small Bowel Inflammation in Patients with Crohn's Disease. (11th October 2021) - Daoud, Nader D; Hashash, Jana G; Picco, Michael F; Farraye, Francis A
Abstract: Background: Severe Crohn's disease [CD] can result in extensive bowel resections and need for creation of an ileostomy. Faecal calprotectin [FC] is well studied in CD management, though its role in patients who have an ileostomy is unclear. Our aim is to understand if FC is a useful adjunct to radiographic or endoscopic studies in identifying recurrent CD after surgery in patients with an ileostomy. Methods: Between January 1, 2017, and September 30, 2020, we searched the Mayo Clinic electronic medical record retrospectively for adult patients with ICD-10 code for CD, and a surgical history of an ileostomy. Patients were included in the analysis if they had at least one FC measured and a concomitant radiographic imaging and/or endoscopic procedure. An abnormal FC was defined as greater than 60 µg/g. Results: Of 51 patients who met our inclusion criteria, 17 had an FC level >60 µg/g. Of these 17 patients, 14 had imaging and/or an ileoscopy confirming the presence of small bowel inflammation, with a sensitivity of 87.5%. Of the remaining 34 patients with an FC level ≤60 µg/g, 32 patients had imaging and/or ileoscopy demonstrating no small bowel inflammation, with a specificity of 91.4%. FC from an ileostomy effluent had a positive predictive value of 82.3%, a negative predictive value of 94.1% and test diagnostic accuracy of 90.1%. Conclusion: FC from an ileostomy effluent is a highly sensitive and specific test for the assessment and monitoring of small bowel inflammation and disease recurrence in patients with CD.